Computational modelling of concrete structures : proceedings of the EURO-C 2006 Conference, Mayrhofen, Austria, 27-30 March 2006 - Proceedings of the EURO-C 2006 ( 2006 : Mayrhofen, Austria); Meschke, Gunther (London, UK : Taylor & Francis, 2006)
09